Remote sensing and land & village maps within participative projects in Africa - (:unkn) unknown (My University, 2001)
Participative approaches intended to promote the initiatives of the local populations are widely used in "developing countries". Several methods and tools were elaborated, in particular for the diagnosis and the economic planning. Within the framework of development projects carried out by FAO, and of specific meetings with actors of the development in West Africa (NGO, engineering companies, funding institutions), several types of spatial representations could be tested. We present here the case of black and white imagemaps derived from satellite images and the case of village-level maps. These experiments show that the mentioned spatial representations constitute evident supports of communication and of negotiation : they materialize on a visual and public document a local reality expressed collectively and whose stakes can then be discussed and negotiated. It remains to improve the insertion of these representations in the planning and the progress of the projects of development and to more finely study the stakes of these collective representations. It remains also to establish parallel with methods of territorial development employed in France.
Keywords: African Research